2014
DOI: 10.1016/j.jmatprotec.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A Process/Machine coupling approach: Application to Robotized Incremental Sheet Forming

Abstract: International audienceIn this paper, a Process/Machine coupling approach applied to Robotized Incremental Sheet Forming (RISF) is presented. This approach consists in coupling a Finite Element Analysis (FEA) of the process with an elastic modelling of the robot structure to improve the geometrical accuracy of the formed part. The FEA, assuming a rigid machine, is used to evaluate the forces at the interface between the tool and the sheet during the forming stage. These forces are used as input data for the ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
(35 reference statements)
1
22
0
Order By: Relevance
“…Chera et al [31] investigated the capacity of Kuka industrial robot during the SPIF process in terms of forming forces. The results showed that maximum value of force in the axial direction was close to 230 N and force capacity of the Kuka KR6 robot was approximately 310 N. Jeremy et al [32] and Belchior et al [33] compared the forming forces obtained from industrial robot with those obtained from a three-axis milling machine on AA5086-H111 sheets. Results showed that the forming force obtained from CNC milling machine setup was 30% more than that produced by industrial robot as given in Table 1.…”
Section: Forming Machinery and Forming Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Chera et al [31] investigated the capacity of Kuka industrial robot during the SPIF process in terms of forming forces. The results showed that maximum value of force in the axial direction was close to 230 N and force capacity of the Kuka KR6 robot was approximately 310 N. Jeremy et al [32] and Belchior et al [33] compared the forming forces obtained from industrial robot with those obtained from a three-axis milling machine on AA5086-H111 sheets. Results showed that the forming force obtained from CNC milling machine setup was 30% more than that produced by industrial robot as given in Table 1.…”
Section: Forming Machinery and Forming Forcementioning
confidence: 99%
“…Some researchers [5,26,27,54] used purpose-built machines that have been designed especially for the SPIF process. It is clear from Table 1 that the high flexibility and fast drives of robots are favorable in the ISF process in order to produce components at a forming force less than that obtained with the CNC milling machine [33]. Hence, industrial robots consume less power as compared to CNC milling machine and make the ISF process economical.…”
Section: Forming Machinery and Forming Forcementioning
confidence: 99%
“…However, the major disadvantage is the less precision of the tool position; especially under high loads condition that limit robot arm capabilities in ISF operations. Belchior et al [13] and I.…”
Section: Introductionmentioning
confidence: 95%
“…On a NC milling machine, the execution of such finishing pass in a relatively short production time requires the use of the 4-axis mode allowing the rotation of workpieces about the Z-axis (tool axis). 13 (a) (b) (c) Fig 14. (a) Dome with double pass SPIF-T using 0.2 mm increment penetration, (b) and (c) dome after a finishing pass…”
Section: Effect Of the Penetration Incrementmentioning
confidence: 99%
“…The first one is an adaptive blank holder that acts in the vicinity of the forming tool and reduces unwanted secondary deformation that would lead to deviations from the target geometry. Belchior et al (2014) applied Process/Machine coupling approach to Robotized Incremental Sheet Forming (RISF) for Finite Element Analysis (FEA) of the process with an elastic modeling of the robot structure to improve the geometrical accuracy of the formed part. Lu et al (2013) presented a new feature-based tool path generation algorithm for incremental sheet forming process in which tool paths are generated according to the specified critical edges to improve geometric accuracy.…”
mentioning
confidence: 99%